THE EFFECT OF GENDER ON RIGHT VENTRICULAR DEFORMATION IN UNTREATED HYPERTENSIVE PATIENTS. (June 2018) - Tadic, M.; Cuspidi, C.; Ivanovic, B.; Pencic, B.; Grassi, G.; Bombelli, M.; Celic, V.
Abstract : Objective: The purpose of this investigation was to evaluate the effect of gender on right ventricular (RV) strain in hypertensive individuals. Design and method: This cross-sectional investigation involved 178 untreated hypertensive subjects and 94 normotensive controls. All study participants underwent 24-hour ambulatory blood pressure monitoring and detailed echocardiographic assessment that included strain evaluation. Results: The difference in 24-h blood pressure was not found between hypertensive men and women. RV wall thickness was higher among hypertensive participants, but there was no significant difference between hypertensive women and men (4.7 ± 0.5 vs. 4.9 ± 0.7 mm, p = 0.108). RV global longitudinal strain was significantly lower in hypertensive subjects comparing with controls (−22.8 ± 2.6 vs. −25.6 ± 3.4 %, p < 0.001). RV global longitudinal strain was significantly lower in hypertensive men than in women (−21.4 ± 2.1 vs. −24.0 ± 3.1 %, p < 0.01). Layer-specific RV strain showed that endocardial and mid-myocardial longitudinal strains were significantly lower in hypertensive population. Additionally, RV endocardial longitudinal strain was significantly lower in hypertensive men than in hypertensive women (−23.2 ± 2.8 vs. −25.8 ± 3.4 %, p < 0.001). Female gender and arterial hypertension and their interaction were related with reduced RV global and endocardial longitudinal strain. Conclusions: RV longitudinal strain and RV layer-specific endo- and mid-myocardial strains were significantly reduced in hypertensive patients. Female gender was associated with significantly higher risk of decreased RV longitudinal and endocardial strain.